A pH optode based on thymol blue: application to determination of CO2 using flow injection analysis system - Sotomayor, Maria Del Pilar Taboada; Raimundo Júnior, Ivo Milton; Rohwedder, Jarbas José Rodrigues; Oliveira Neto, Graciliano (Eclética Química, 2010)
An optode based on thymol blue (TB), an acid-based indicator, has been constructed and evaluated as a detector in FIA system for CO2 determination. The dye was chemically immobilised on the surface of a bifurcated glass optical fibre bundle, using silanisation in organic media. In FIA system, hydrogen carbonate or carbonate samples are injected in a buffer carrier solution, and then are mixed with phosphoric acid solution to generate CO2, which diffuses through a PTFE membrane, in order to be collected in an acceptor carrier fluid, pumped towards to detection cell, in which the optode was adapted. The proposed system presents two linear response ranges, from 1.0 x 10-3 to 1.0 x 10-2 mol l-1, and from 2.0 x 10-2 to 0.10 mol l-1. The sampling frequency was 11 sample h-1, with good repeatability (R.S.D < 4 %, n = 10). In flow conditions the optode lifetime was 170 h. The system was applied in the analysis of commercial mineral water and the results obtained in the hydrogen carbonate determination did not differ significantly from those obtained by potentiometry, at a confidence level of 95 %.